Visualizing Vocabulary and Communicative Competence: The Use of Picture Word Media among Seventh-Grade Students - Agustina Susanti Ina; Hernina Dewi Lestari; Yahmun Yahmun (Explorations in English Learning, 2026)
Although vocabulary is a fundamental component of English language learning, many EFL students still experience limited vocabulary mastery and low communicative competence, particularly in classroom contexts where instruction remains teacher-centered and lacks visual support. This gap highlights the need for effective instructional media that can enhance both vocabulary acquisition and communicative ability simultaneously. This study aimed to improve students’ vocabulary mastery and communicative competence through the use of picture word media among seventh-grade students at SMP Swasta Bukambero in the 2024–2025 academic year. The research employed Classroom Action Research (CAR) conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 32 seventh-grade students. Data were collected through observations, interviews, and vocabulary tests (pre-test and post-test). The findings showed a significant improvement in vocabulary mastery: the pre-test mean score was 43 (13% passing), Cycle I increased to 70 (56% passing), and Cycle II reached 83 (90% passing). Classroom observations and interviews also indicated improved communicative competence, as students became more active, confident, and engaged in classroom interaction. They demonstrated better understanding of vocabulary, increased participation in discussions, and improved ability to express ideas. The learning process also shifted toward a more student-centered environment. Therefore, picture word media is effective in improving vocabulary mastery and supporting communicative competence in EFL learning.